Illustrated dental embryology, histology, and anatomy / Margaret J. Fehrenbach, Tracy Popowics. - Fehrenbach, Margaret J.; Popowics, Tracy (Maryland Heights, Missouri Elsevier Saunders, 2016)
'Updated and expanded evidence-based coverage includes topics such as caries risk, fetal alcohol syndrome, periodontal disease, thyroid hormones and disease, stem cells and dental pulp, and developmental defects associated with specific diseases and conditions.'--Publisher description.
unit I. Orofacial structures -- 1. Face and neck regions -- 2. Oral cavity and pharynx -- unit II. Dental embryology -- 3. Prenatal development -- 4. Face and neck development -- 5. Orofacial development -- 6. Tooth development and eruption -- unit III. Dental histology -- 7. Cells -- 8. Basic tissues -- 9. Oral mucosa -- 10. Gingival and dentogingival junctional tissue -- 11. Head and neck structures -- 12. Enamel -- 13. Dentin and pulp -- 14. Periodontium : cementum, alveolar process, and periodontal ligament -- unit IV. Dental anatomy -- 15. Overview of the dentitions -- 16. Permanent anterior teeth -- 17. Permanent posterior teeth -- 18. Primary dentition -- 19. Temporomandibular joint -- 20. Occlusion.
Previous edition: Mary Bath-Balogh, Margaret J. Fehrenbach. 2011.
Includes bibliographical references (pages 299-300) and index.
Keywords: Tooth -- anatomy & histology; Tooth -- embryology; Mouth -- anatomy & histology; Mouth -- embryology